The Long-Term Impact of the Subprime Mortgage Crisis on Housing Inequality in the United States - Zajícová, Tereza (2025)
his thesis examines how the Great Recession, triggered by the collapse of the U.S. housing bubble and the disruption of mortgage-backed securities (MBS) and related structured products, affected income inequality in the United States. The study situates the crisis within broader theoretical frameworks of financial crises and links macro-financial instability to distributional outcomes. Using pre-tax national income data and inequality measures, the analysis compares three periods—pre-crisis, crisis, and post-crisis—to assess whether the shock altered the structure of income distribution and accelerated polarization across income groups. The empirical section focuses on changes in income shares, with particular attention to the relationship between the top 10% and the bottom 50% of the distribution. The results suggest that the crisis period was associated with measurable shifts in inequality, while the post-crisis years indicate a stronger divergence between higher- and lower-income groups than in the pre-crisis era. These findings support the view that financial crises can have persistent distributional consequences through asset price dynamics, credit conditions, and uneven recovery patterns. The thesis contributes to the literature by combining crisis theory with distributional macroeconomic evidence and by offering a structured comparison of inequality trends across key phases of the Great Recession.